Naïve conceptions about multimedia learning: a study on primary school textbooks - Colombo, Barbara; Antonietti, Alessandro (Frontiers in Psychology, 2013)
HIGHLIGHTS This interview study explores beliefs about the instructional role of illustrations We compared illustrators', teachers', students' and common people's ideas Participants' responses were internally coherent and close to multimedia learning theory We propose and discuss an integrated multimedia learning model An interview study, based on specific pictures taken from textbooks used in primary schools, was carried out to investigate illustrators', teachers', students', and common people's beliefs about the role that illustrations play in facilitating learning. Participants' responses were internally coherent, indicating a systematic nature of the underlying naïve conceptions. Findings disprove Mayer's pessimistic claim that laypersons' conceptions of multimedia learning fail to match experimentally supported principles and theories. On the contrary, interviewees spontaneously came very close to the multimedia learning theory, which states that students learn better from pictures, which fit specific cognitive principles. Implications for school instruction are highlighted.